Sensory Processing dysfunctions of children With Autism Spectrum Disorder and it’s Relative with Some Variables - Abo Hasan, Fadia (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This study aims to investigate the prevalence of sensory processing dysfunctions by the sample of Children With autism spectrum disorder and it’s relative with some variables(age, severity of autism).The researcher adopted the descriptive approach to achieve the aim of the study. The sample consisted of (30) child the range of (3-10) years selected randomly. The researcher used Sensory Profile to explore the sensory processing dysfunctions, consisted of (65) items distributed on (6) domains (Auditory Processing, Visual Processing, Vestibular Processing, Touch Processing, Multisensory Processing, Oral Sensory Processing). The results of the study indicated )66.67%) of autistic children in this sample had sensory processing dysfunctions, There are significant statistical differences at the level of (0.05) between the children in the study sample on The Sensory Profile attributed to autism severity on the whole of a scale domains and on the four subdomains, There are no significant statistical differences at the level of (0.05) between the children in the study sample on the Sensory Profile attributed to age on the whole of a scale domains and on the subdomains. Based on the findings of the study the researcher pointed out the need of comparison studies about the prevalence the sensory processing dysfunctions between (children ,teenager, adult), and another studies as the relation between sensory processing dysfunctions and the adaptive behavior dysfunctions.